The strategic importance of human resources management and the roles of human capital investment and education - Vokoun, Marek; Caha, Zdeněk; Straková, Jarmila; Stellner, František; Váchal, Jan (Univerzita Pardubice, 2018)
The entry focuses on the issue of strategic importance of human resource (HR) management. The questionnaire survey was aimed at companies from the Region of South Bohemia. The approach to personnel agenda was analysed, as well as the connections to the branches in which the tested businesses were active, the size of the company, the education level of their HR officers, and their company level investments in human capital. A high level of heterogeneity in the data was found and no statistical differences were found in tested hypotheses. However, it was discovered that if the HR department employees have tertiary education, it is a sign of a higher standard and competence level of the department. The higher level of competency and HR planning independence was found in the service sector. This supports the claim that a vast variety of skills is needed in order to provide agenda of life-long learning and professional growth.
Keywords: Czech republic; region of South Bohemia; human resources management; personnel department; human resources officer; human capital; O15; J24; I21